Regulation of Steroidogenic Acute Regulatory Protein Transcription in Largemouth Bass by Orphan Nuclear Receptor Signaling Pathways - Kocerha, Jannet (The Endocrine Society, 2010)
The steroidogenic acute regulatory (StAR) protein mediates the rate-limiting step of mitochondrial transport of cholesterol for steroid biosynthesis. To investigate the regulation of this protein in lower vertebrates, we cloned the StAR coding region from large-mouth bass for analysis. Induction of the mRNA corresponded with increasing levels of plasma sex steroids in vivo. Cultures of largemouth bass ovarian follicles were exposed to dibutyryl cAMP (dbcAMP), a potent signaling molecule for steroidogenesis. StAR mRNA expression was significantly up-regulated by dbcAMP signaling, suggesting that the 5′ regulatory region of the gene is functionally conserved. To further analyze its transcriptional regulation, a 2.9-kb portion of the promoter was cloned and transfected into Y-1 cells, a steroidogenic mouse adrenocortical cell line. The promoter activity was induced in a dose-responsive manner upon stimulation with dbcAMP; however, deletion of 1 kb from the 5′ end of the promoter segment significantly diminished the transcriptional activation. A putative retinoic acid-related receptor-α/rev-erbα element was identified between the −1.86- and −2.9-kb region and mutated to assess its potential role in dbcAMP regulation of the promoter. Mutation of the rev-erbα element significantly impeded dbcAMP-induced activation. Chromatin immunoprecipitation and EMSA results revealed rev-erbα and retinoic acid-related receptor-α enrichment at the site under basal and dbcAMP-induced conditions, respectively. These results implicate important roles for these proteins previously uncharacterized for the StAR promoter. Altogether these data suggest novel regulatory mechanisms for dbcAMP up-regulation of StAR transcription in the distal part of the largemouth bass promoter.